FORESTS AND TRIBAL MEDICINES - Abraham, Adlin (International Journal of Research -GRANTHAALAYAH, 2026)
When human beings first appeared on Earth, their lives were entirely dependent on forests. They lived within forest environments, and roots, fruits, and leaves obtained from forests formed their food. Large leaves were used to cover the body. Messages were sent from one place to another using natural materials, and forest-based medicines were widely used. Since ancient times, tribal communities have maintained a close and interdependent relationship with forests. Nearly seven crore tribal people in the country — about seventy percent of whom live within or near forests — have traditionally depended on forest resources and forest land. Because of their close association with forests, tribal communities possess deep knowledge of trees and plants and are well acquainted with the medicinal uses of forest herbs.